Together Against Hypertension: A Community Blood Pressure Screening and Education Program - Yosi Oktarina; Riska Amalya Nasution; Yulia Indah Permata Sari; Veni Misriyani; Lisa Anita Sari; Rts. Netisa Martawinarti; Rina Oktaria; Febiyora Chandra Kirana; Putri Irwanti Sari; Nurhusna, Nurhusna; Yurni, Yurni; Meinarisa, Meinarisa (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Hypertension is a significant global public health concern that often remains asymptomatic in its early stages, emphasizing the need for proactive prevention and management strategies. This community service program, Together Against Hypertension, was conducted in Jambi City in collaboration with the Nursing Student Association of Universitas Jambi, aiming to enhance public awareness of hypertension and identify individuals at risk through targeted blood pressure screenings. The program employed a two-pronged approach: (1) educational sessions focused on the etiology, risk factors, complications, and prevention of hypertension, with an emphasis on lifestyle modifications; and (2) blood pressure screenings to detect undiagnosed hypertension or prehypertension cases within the community. Participants included diverse demographic groups, with nursing students acting as facilitators under professional supervision. The findings revealed that 35% of participants exhibited elevated blood pressure, with 20% previously unaware of their hypertensive status. Educational activities significantly improved participants' understanding of hypertension and its management, fostering greater adherence to regular monitoring and healthy behaviors. This initiative underscores the importance of community-based interventions in addressing hypertension and provides a scalable model for similar programs aimed at improving population health outcomes.